A comparative study on the effects of 2%, 5% and 8% concentrations of glutaraldehyde on pulpotomy-treated rat teeth - Navarrete, Elaine M.; Tan, Edelmira G.; Caparas, Corazon Lourdes (Adviser).
Glutaraldehyde, a commonly used fixative agent in electron microscopy and chemical agent for sterilization, has been proven in many researches to be an ideal substitute to formocresol as a fixative agent in vital pulp therapy. The purpose of this study is to determine the concentration at which glutaraldehyde would be most effective and yield the most favorable result following pulpotomy procedures. Three concentrations of glutaraldehyde were tested, i.e. 2%, 5% and 8%, on caries-free maxillary and mandibular first molars of nine Sprague Dawley rats. Histologic assessment of the remaining pulpal tissue on one and four week intervals showed a trend between the three tested concentrations. A greater depth of fixation was demonstrated as the concentration of glutaraldehyde was increased. Fixation were all limited within the pulp canal. It was also observed that the higher the concentration, the lesser was the degree of inflammation present within the pulp. Assessment on the eight-week interval was not possible due error in the sectioning of the specimens.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Glutaraldehyde